Counselor academic training, counseling experience, and counselor self-efficacy as predictors of counselor psychological well-being - Hoang, Minh To Nga (Animo Repository, 2020)
The mixed methods sequential explanatory study was conducted to determine whether counselor academic training, counseling experience, and counselor self-efficacy are significant predictors of counselor psychological wellbeing and its related sub-domains (e.g. autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance). 93 Filipino practicing counselors who have at least masteral units in Counseling Psychology or related degree programs, and who vary in counseling experience participated in this research which includes two studies: the quantitative study and the qualitative study. A personal profile sheet, the Counselor Activity Self-Efficacy Scale, and the Psychological Well-being Scale were used as instruments to gather data for the quantitative study, in which descriptive and inferential statistics (e.g. Spearman's Rho, Pearson r, and stepwise regression) were computed for data analysis. Based on the results of the quantitative study, 11 respondents, 6 with the highest and 5 with the lowest psychological well-being scores, were recruited for the qualitative study, which employed in-depth interviews as the way of gathering data. Integration of findings from both studies revealed that only counseling experience and counselor's self-efficacy are significant predictors of psychological well-being of counselors, with counselor self-efficacy being the better predictor of counselors psychological well-being. Implications of the study and various iv recommendations were made for possible interventions to enhance the counselor psychological well-being and related future research.